Development of enhanced ultra wideband antenna designs and rake receivers for indoor wireless systems - Rashid Ali Fayyadh (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2014)
In this thesis, five UWB antenna designs and five UWB rake-receiver structures are proposed to cover the entire UWB frequency range (3.1-10.6 GHz) as defined by Federal Communication Commission (FCC) that consequently provides many challenges in the wireless communication area including antenna design and receiver scheme. These proposed antennas have small sizes and improved gain and radiation efficiency compared with the literature ones and the performances are analyzed under several antenna parameters to guarantee that the transmitted signal will be correctly recovered at the receiver end.